2021
DOI: 10.1002/lt.26311
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of In‐Hospital Mortality in Decompensated Cirrhosis with Acute‐on‐Chronic Liver Failure

Abstract: Acute‐on‐chronic liver failure (ACLF) is a condition in cirrhosis associated with organ failure (OF) and high short‐term mortality. Both the European Association for the Study of the Liver‐Chronic Liver Failure (EASL‐CLIF) and North American Consortium for the Study of End‐Stage Liver Disease (NACSELD) ACLF definitions have been shown to predict ACLF prognosis. The aim of this study was to compare the ability of the EASL‐CLIF versus NACSELD systems over baseline clinical and laboratory parameters in the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
5
13
0
Order By: Relevance
“…In this case, the situation was even more challenging because this was a new diagnosis of cirrhosis and the patient himself was obtunded. The ICU, hepatology team, and family would benefit from guidance from the palliative care service if available, especially using the NACSELD-ACLF score, which is associated with futility (16–18). This is because liver transplant candidacy depends on multiple factors.…”
Section: Casementioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the situation was even more challenging because this was a new diagnosis of cirrhosis and the patient himself was obtunded. The ICU, hepatology team, and family would benefit from guidance from the palliative care service if available, especially using the NACSELD-ACLF score, which is associated with futility (16–18). This is because liver transplant candidacy depends on multiple factors.…”
Section: Casementioning
confidence: 99%
“…The ICU, hepatology team, and family would benefit from guidance from the palliative care service if available, especially using the NACSELD-ACLF score, which is associated with futility (16)(17)(18). This is because liver transplant candidacy depends on multiple factors.…”
mentioning
confidence: 99%
“…Furthermore, to be categorized as ACLF, patients need to have at least 2 EASL‐CLIF OFs. Despite the assertion that “restricting the analysis to only include patients with ≥2 OFs would be against the spirit of the EASL‐CLIF consortium,” ( 2 ) methodologically speaking it would be ideal if the authors provided a secondary analysis to have a head‐to‐head comparison of participants who only had the same OFs, excluding everyone else.…”
Section: Of Nacseld Easl‐clifmentioning
confidence: 99%
“…Wong et al led an analysis of 1031 patients from the North American Consortium for the Study of End‐Stage Liver Disease (NACSELD) and compared 2 different syndrome definitions of ACLF to predict in‐hospital mortality. ( 2 ) Wong et al used the European Association for the Study of Liver Consortium of Liver Failure (EASL‐CLIF), which has 6 organ failure (OF) components, ( 3 ) versus the NACSELD with 4 OF components. ( 4 ) Using the areas under the receiver operating characteristic curve (AUROCs) derived from multivariate logistic regressions, they concluded that either the EASL‐CLIF or NACSELD criteria had a similar discriminatory ability to predict in‐patient hospital mortality compared with a model with age, white blood cell count, and Model for End‐Stage Liver Disease (MELD).…”
Section: Of Nacseld Easl‐clifmentioning
confidence: 99%
“…1 Asian Pacific Association for Study of Liver Diseases (APASL) provided the first consensus, 2 on ACLF in 2009 and later on modified the definition in 2014. In the study by APASL, patients with already decompensated cirrhosis who deteriorated due to acute insult were excluded but other organizations e.g., European Association for Study of Liver Diseases (EASL), 3 and North American Consortium for Study of End-stage Liver Disease (NACSELD) 4 included such patients in their definitions of ACLF.…”
Section: Introductionmentioning
confidence: 99%